Reading as a Foundation for Developing Human Abilities - Fitrianingsih; Runtao, Zha; Nugraha, Rahmat Mulya (International Journal of Language and Culture, 2025)
The importance of reading as a basis for honing human abilities. Reading is a fundamental basic skill, becoming the basic foundation for various aspects of life, including learning, understanding, and personal development as well as improving language comprehension. Strong reading skills enable a person to master a field of study, access a lot of information, and broaden their horizons. The purpose of this study is so that researchers can invite readers to apply the mindset that reading plays a very important role in honing human abilities. Learning to read must be applied early on, and made a habit. Even though you can read, if you don't use it and don't make it a habit, it's useless. If someone can't read, the impact can be very broad, ranging from difficulty in learning, difficulty communicating, to lack of insight and critical thinking skills.